Predicting Video Game Addiction: The Effects of Composite Regulatory Focus and Interpersonal Competence Among Indonesian Teenagers During COVID-19 Pandemic: Array - Yudhi Purwa Nugraha; Awalya Awalya; Mulawarman Mulawarman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2021)
Video game addiction is recognized as a mental health problem caused by uncontrolled access to video gaming platforms. Proper assistance and counseling programs based on the addiction causing factors are required to reduce the tendencies of video game addiction. The study aims to identify the correlation between regulatory focus theory and interpersonal competence towards the tendencies of video game addiction. The study is a type of cross-sectional research with the adapted psychological scales. A total of 136 teenagers, consisting of 86 males and 50 females participated in the survey of self-reported video game addiction. The data were analyzed using multiple regression analysis. The findings revealed that regulatory focus and interpersonal competence simultaneously had a significant effect on the tendencies of video game addiction behavior. The findings of the study can provide the basis to provide proper assistance services, in an attempt to reduce the tendencies of video game addiction among teenagers.